Poverty in Malawi: Current status and knowledge gaps - Mussa, Richard; Pauw, Karl (International Food Policy Research Institute, 2011)
As in many developing countries, poverty reduction is a primary development goal in Malawi. The country is committed to the Millennium Development Goals (MDGs), which seek, among other things, to eradicate extreme poverty and hunger. Over the years, the Malawian government has pursued poverty reduction efforts through various strategies emphasizing economic growth, infrastructural development, and the provision of basic social services. These strategies have included: the Poverty Alleviation Program (1994); the Malawi Poverty Reduction Strategy (2002-2005); and, more recently, the Malawi Growth and Development Strategy (MGDS) (2006-2011 and 2011-2016). Despite these various policies and measures, poverty remains widespread in Malawi. This brief reviews the poverty literature and data in Malawi with the aim of developing a poverty profile, describing recent poverty trends, and identifying the determinants of poverty. Based on the analysis, existing knowledge and research gaps are identified and briefly discussed.